Good practices for diversity, livelihoods and ecosystem services: what can we learn from tropical fruit farming communities in Asia? - Sthapit, B.; Lamers, H.; Ramanatha Rao, V. (2011)
This poster describes a selected set of good practices for diversity maintenance that were studied and systematically documented from 36 communities in India, Indonesia, Malaysia and Thailand as part of the ‘Conservation and Sustainable Use of Cultivated and Wild Tropical Fruit Diversity: Promoting Sustainable Livelihoods, Food Security and Ecosystem Services’ project. Farmers have several good reasons for maintaining and using diverse traditional tropical fruit species and varieties. They have developed a wide range of mechanisms to make optimal use of local diversity for their own well-being and benefit. We often claim to understand the benefits of diversity for farmers and rural households, yet there are very few systematic studies and hardly any empirical evidence to back this up.